Mycelium-based bioproducts: A novel material for a sustainable economy – A comprehensive review - Rahim Khan (The Microbe, 2025)
The biodesign and biofabrication of biomaterials from lignocellulosic plant residues self-generated by fungal mycelium have emerged as a new material culture in the past two decades. This new material culture is based on alternative manufacturing paradigms that prioritize making new materials instead of extracting them. This culture integrates the basic principles of the circular economy and material biotechnology, ensuring their susceptibility to biodegradation and returning to their original state. Its implementation in manufacturing sectors aims to compete with animal-based leather, materials, and petrochemical products while promoting sustainable protein foods, reducing global environmental impact. This review explores the molecular and global aspects of new mycelial culture, focusing on the morphogenesis, chemical composition, and cellular integrity of fungi. It discusses the extracellular multienzymatic systems for lignocellulose degradation, the main substrates used, biomaterials developed from mycelium, biotextiles, materials, packaging and insulation products, new food sources, and art and architectural design. The review also highlights the current state of the art of the avant-garde companies promoting a circular economy based on fungal mycelium, replacing fossil resources with environmentally friendly materials, generating sustainable production cycles with low energy demand and environmental impacts, and promoting a new material consciousness.